2019
DOI: 10.1007/s10344-019-1310-6
|View full text |Cite
|
Sign up to set email alerts
|

The value of by-catch data: how species-specific surveys can serve non-target species

Abstract: Camera trapping has a wide range of research application but, while research designs are often focused on the study of a single focal species, cameras can also record other non-target species. Occupancy modelling using bycatch data can be a valuable resource to gain information on these species maximizing the scientific effort and efficiency of wildlife surveys. In this study we used by-catch data from a European wildcat (Felis sylvestris sylvestris) survey in Southern Italy to assess the habitat covariates de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 40 publications
0
15
0
2
Order By: Relevance
“…We utilised camera trap images of brown hyaenas collected by these camera traps (bycatch data) to model the population density of brown hyaenas. Analysing bycatch data is an efficient use of resources in conservation, provided species-specific methodological discrepancies are considered and accounted for 46,55,56 . Bycatch data on brown hyaenas from camera traps initially set up to survey leopards were used to successfully conduct occupancy analysis 46 .…”
Section: Methodsmentioning
confidence: 99%
“…We utilised camera trap images of brown hyaenas collected by these camera traps (bycatch data) to model the population density of brown hyaenas. Analysing bycatch data is an efficient use of resources in conservation, provided species-specific methodological discrepancies are considered and accounted for 46,55,56 . Bycatch data on brown hyaenas from camera traps initially set up to survey leopards were used to successfully conduct occupancy analysis 46 .…”
Section: Methodsmentioning
confidence: 99%
“…We used a photographic dataset from a research project targeting leopard. Considering the logistical and budget requirements of camera trapping, this study illustrates the value of by-catch data in terms of resource optimisation, provided that the survey design also complies with the ecology of the non-target species [66]. In this study, the conservative trap layout with an average distance between stations of around 2 km was compatible with the home ranges of the species we considered [67,68], and allowed individuals’ recapture at multiple camera trap stations [69].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, interspecific interactions can be predicted, even with effects on rodent populations [56][57][58]. Up until now, most studies on rodent-ungulate interactions have been conducted on small rodents, with very few studies involving large ones [42,45]. Large-sized rodents would require a higher food amount with respect to small-sized ones, thus enhancing the potential for competition with other herbivores.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we reported, for the first time, some patterns of direct aggressive interactions between a large rodent and a cervid, i.e., the roe deer. Porcupines become particularly intolerant toward other species and conspecifics in cold months, i.e., at the peak of their reproductive period, both in feeding areas and in the surroundings of their burrows [42][43][44]. In cold months, harassments by crested porcupines (quill/crest erection) have been observed against wild boar, Sus scrofa, in feeding areas, and, in a few cases, wild boars have been wounded by porcupine quills (e.g., in Alta Val d'Elsa, A. Pieragnoli, personal communication 2020, [38]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation